2014
DOI: 10.1007/s10943-014-9827-1
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation of the Effects of Psycho-Spiritual Integrative Therapy on Breast Cancer Survivors’ Experience of Paradox

Abstract: This study is an exploratory, qualitative investigation of breast cancer survivors' experiences of paradox, following psycho-spiritual integrative therapy (PSIT). Previous studies examined the role of paradox in spiritual development among women diagnosed with cancer; this study investigated a psycho-spiritual intervention for multicultural cancer survivors. Twelve multicultural breast cancer survivors, from a sample of 30 women participants in an 8-week PSIT group intervention, were recruited from oncologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
2
4
0
1
Order By: Relevance
“…Similarly, data from Whitford and Olver demonstrated that two terms often used to describe spiritual well-being, peace and meaning, were associated with quality of life perceptions among newly-diagnosed cancer patients [ 45 ]. Our data support findings by Patel [ 46 ] who reported that breast cancer survivors experience spiritual growth and development after experiencing cancer. Furthermore, the reliance on positive spiritual and religious beliefs relates to our worldview theme, suggesting these two variables were connected and inter-dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, data from Whitford and Olver demonstrated that two terms often used to describe spiritual well-being, peace and meaning, were associated with quality of life perceptions among newly-diagnosed cancer patients [ 45 ]. Our data support findings by Patel [ 46 ] who reported that breast cancer survivors experience spiritual growth and development after experiencing cancer. Furthermore, the reliance on positive spiritual and religious beliefs relates to our worldview theme, suggesting these two variables were connected and inter-dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with those reported by Delgado-Guay et al (9) and Patel et al (8). In the study conducted by Delgado-Guay et al (9), it was observed that spiritual pain, as a sign of low religiosity/spirituality, had a negative effect on the physical/emotional symptoms of cancer patients and was positive correlated with the psychological distress of these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Although in some research, religiosity and spirituality were considered as separate terms (6), in the present study, they were not separated and were addressed as a whole (15). An important concept for coping with chronic diseases, including cancer, is illness perception, which is considered an important causative factor for the consequences of the disease, such as psychological distress and quality of life (2,8,16,17). According to the Common-Sense Model of Self-Regulation developed by Leventhal et al, patients perceive a health threat by promoting their own cognitive representations about the disease and its treatment based on previous information and experiences with the disease (16).…”
mentioning
confidence: 99%
“…Despite the death-like experiences of breast cancer diagnosis and treatment, Grogan and Mechan [27] found that younger women who underwent mastectomy were able to find acceptance by separating themselves mentally from the breast that was removed and embracing the sick role. Patel et al [42] also found that psycho-spiritual integrative therapy (PSIT) helped breast cancer survivors let go of old ways of being and embrace the sick role. Therefore, Jung's rebirth experience stage of the individuation theory may also be a necessary component in the cancer treatment journey.…”
Section: Stage 1 Of Individuation Death-experiencementioning
confidence: 99%